Feasibility and accuracy of 64-row MDCT coronary imaging from a centre with early experience : a review and comparison with established centres - Ong, K.; Chin, SP; Chan, W.L; Liew, C.K; Seyfarth, M.T; Liew, H.B; Rapaee, A.; Sim, K.H (Medical Journal of Malaysia, 2005)
Ong K., Chin SP., Chan WL., Liew CK., Seyfarth MT., Liew HB., Rapaee A., Sim KH.